THEORETICAL STUDY OF THE BIOLOGICAL ACTIVITY OF 1,6-BIS (4-BROMOPHENOXY) HEXA-2,4-DIINE - Medeu Azamatovich Abatov (Journal Park Publishing, 2024)
Today, in the process of studying the composition of each chemical compound, its biological activities are also fully studied. In recent years, many substituted diaryldipropargyl esters with different biological activities have been synthesized and their biological activities have been studied. In this study, it was found that some substituted arylpropargyl ester compounds have enzyme-inhibiting, hormone-stimulating, and skeletal muscle-relaxing properties that catalyze many biochemical reactions. It is known that today biological research requires a lot of money, therefore, in this study, the results of the study of the biological activities of 1,6-bis(4-bromophenoxy) hexa-2,4-diine through the PASS (online) program are presented.
Keywords: pharmacological activity, pharmacological inactivity, Pass (Prediction of activity spectra for substances), biological activity, inhibitor, diaryldipropargyl esters.